Governed for God's praise - Robinson, David (Country Life, 2022)
The Abbey of St Mary and St Nicholas at Beeleigh was founded towards the end of the 12th century for a community of Premon-stratensian canons, named after the mother house of their order, Premontre (Aisne), in north-eastern France. With the support of Robert Mantell (d. 1190), lord of Little Marlow and sheriff of Essex, the canons were settled on the river Chelmer, a short distance upstream from the market town of Maldon. [...]in 1249, William de Fancourt and his wife, Rose, granted the canons a plot of land, in return for which during certain Masses-they were to light a candle 'before the heart of St Roger for ever'. Two of the ground-floor spaces are perfect embodiments of comparatively restrained early 13th-century architecture, namely the chapterhouse and the day room.
Place: Bath Publisher: Future Publishing Ltd
Keywords: beeleigh